PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI KECAMATAN KARANG DAPO KABUPATEN MUSI RAWAS UTARA - Supriyanto, Supriyanto; Dahsri, Mohd Fauzan (Jurnal Media Ekonomi (JURMEK), 2019)
The purpose of this study was to answer the effect of leadership and work motivation on employee performance in the Sub District Office of Karang Dapo Sub-District, Musi Rawas Utara Regency. Based on the results of the t test, it can be explained that the leadership variable (X1) on the performance of employees in the Karang Dapo District Office of North Musi Rawas Regency shows that the tcount = 2.572 is greater than the value of ttable 2.021 with a significant level = 0.014 <(α) 0.05, df (n -2) 40 - 2 = 38 is 2,021, this shows Ho is rejected and Ha is accepted and partially the leadership variable has a significant influence on employee performance in the Karang Dapo Sub-District Office of North Musi Rawas Regency. Based on the results of the t test can be explained as follows: that the work motivation variable (X2) on the performance of employees in the Sub District Office of Karang Dapo Subdistrict, North Musi Rawas District shows the tcount = 3,793 is greater than the ttable value of 2,021 with a significant level = 0.001 <(α) 0.05 , df (n-2) 40 - 2 = 38 is equal to 2,021, this shows that Ho is rejected and Ha is accepted and partially the work motivation variable has a significant influence on employee performance in the Sub District Office of Karang Dapo Subdistrict, North Musi Rawas Regency. Based on the Fcount test results obtained are 10.230> Ftable = 3.34 and the significance level simultaneously the significance is 0,000 <(α) = 0.05 df = n - k = 40 - 2 - 1 = 37 is 3.26 so Ho rejected and Ha accepted.